Exploring cell reprogramming techniques for Angelman Syndrome disease modelling - Joaquim, Mariana Isabel Lopes (2017)
Angelman Syndrome (AS) is an imprinted neurodevelopmental disease with no cure caused by the lack of UBE3A expression, which, in neurons, is exclusively maternally expressed. The paternal UBE3A allele is silenced by the UBE3A antisense transcript (UBE3A-ATS), which is only expressed from the paternal chromosome. In AS mouse model, inhibition of the UBE3A-ATS transcription can reactivate paternal UBE3A. To translate such an approach to humans, the development of a cellular model for this disease is necessary. Here we sought to develop cellular model systems of AS from patient-derived fibroblasts and evaluate their imprinting status using RNA FISH-based single-cell approaches. First, a neural direct conversion protocol based on expression of two neuronal transcription factors - ASCL1, NGN2 – and SMAD pathway inhibitors was tried in order to convert fibroblasts into neurons. Despite high infection efficiency and detection of transgenic ASCL1 expression, the generated “iNs” did not show signs of neuronal identity based on RT-qPCR and IF analysis. This failure might have been caused by lack of lentiviruses concentration by ultracentrifugation, antibiotic selection skipping and/or dislodging of the cells under conversion. Second, we tried to generate NPCs from iPSCs using a commercially available differentiation protocol. Based on RT-qPCR and IF analysis, the generated “NPCs” failed to express the correct genetic markers. This failure might be explained by inappropriate accelerated division rate of the cells during induction or lack of pluripotency of the newly-generated iPSCs used. Despite unsuccessful generation of neuronal cells, we were able to optimize nascent-transcript RNA FISH, combining UBE3A and paternally expressed SNORD116, which is a crucial tool to confirm the imprinting status of the Angelman locus in newly-generated cells. With future efforts, the establishment of AS cellular model systems will serve as drug screening platform to test paternal UBE3A reactivation as a therapeutic target for AS.